Performance Comparison and Nutritional Requirements of Five Commercial Layer Strains in Phase IV - Wu, G.; Liu, Z.; Bryant, M.M.; Roland Sr., D.A. (International Journal of Poultry Science, 2005)
Five commercial white egg layer strains (Current-Bovans, Older-Bovans, Oldest-Bovans, Experimental-Bovans, and Dekalb) were used to compare performance and nutrient requirements when fed three protein levels (16.00, 14.85 and 13.99%). There were eight replicates of 15 hens (67 wk of age) for each treatment and the trial lasted 10 weeks. The results showed that there were no interactions between protein and strain on feed intake, egg production, egg mass, egg weight, feed conversion, egg specific gravity, and body weight of hens. Protein had significant effects on feed intake, egg mass, egg weight, egg specific gravity, and body weight. There were significant strain effects on feed intake, egg production, egg mass, egg weight, feed conversion and egg specific gravity. Current-Bovans had the best overall performance among the five layer strains. However, Dekalb had significant higher egg weight compared to Bovans. The best performance of Current-Bovans and Dekalb was obtained with hens fed the diet containing 16.00% protein. Current-Bovans hens required 16.5 g protein, 640 mg TSAA, 856 mg lysine, and 296 kcal ME per hen daily or 0.31 g protein, 12.00 mg TSAA, 16.07 mg lysine, and 5.55 kcal ME per g egg for the best performance. Dekalb hens required 17.8 g protein, 691 mg TSAA, 925 mg lysine, and 319 kcal ME per hen daily or 0.34 g protein, 13.04 mg TSAA, 17.45 mg lysine, and 6.03 kcal ME per g egg for the best performance.